Academic Supervision of Teachers in Preparing Learning Plans at Muhammad Basiuni Imran Sambas Middle School - Nurhalimah; Nuraini; Jaelani (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2024)
This study aims to see teachers preparing learning plans after academic supervision is carried out at Madrasah Tsanawiyah Muhammad Basiuni Imran Sambas. This research method uses a qualitative approach with a descriptive method, namely the researcher describes, explains so that it can describe the state of the object being studied as it is, in accordance with the conditions and situations when the researcher conducts research in the field. This study uses a case study research type, namely the researcher focuses on a case to be observed and analyzed carefully. The results of this study can be concluded that Academic Supervision at Madrasah Tsanawiyah M. Basiuni Imran Sambas on Teachers in Preparing Learning Plans, namely carrying out the stages of planning, implementation, evaluation and follow-up of academic supervision on teachers in preparing learning plans which include syllabus, annual programs, semester programs and learning implementation plans. After academic supervision is carried out on teachers in preparing learning plans, it has an impact on good planning documents and can be used as a guide in implementing learning